Early novels and stories - Baldwin, James (The Library of America, 1998)
James Baldwin's writings on the subject of race in America undeniably made him one of the greatest African American writers of the 20th century. As the civil rights movement gained momentum in the two decades following World War II, Baldwin landed squarely in the public eye, and his prose communicated the hope and frustration of the fight for racial equality